Exploring Capabilities for the Smart Service Transformation in Manufacturing: Insights from Theory and Practice - Koldewey, Christian; Fichtler, Timm; Scholtysik, Michel; Biehler, Jan; Schreiner, Nick; Sommer, Franziska; Schacht, Maximilian; Kaufmann, Jonas; Rabe, Martin; Sedlmeier, Joachim; Dumitrescu, Roman
Digital Servitization is one of the significant trends affecting the manufacturing industry. Companies try to tackle challenges regarding their differentiation and profitability using digital services. One specific type of digital services are smart services, which are digital services built on data from smart products. Introducing these kinds of offerings into the portfolio of manufacturing companies is not trivial. Moreover, they require conscious action to align all relevant capabilities to realize the respective business goals. However, what capabilities are generally relevant for smart services remains opaque. We conducted a systematic literature review to identify them and extended the results through an interview study. Our analysis results in 78 capabilities clustered among 12 principles and six dimensions. These results provide significant support for the smart service transformation of manufacturing companies and for structuring the research field of smart services.
Keywords: Digital Servitization; Transformation; Capabilities; Maturity; Smart Services

Innovative measurement system for saber curvature observation in straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Procedia Computer Science)
Keywords: General Engineering

Evaluating Security Through Isolation and Defense in Depth - Bodden, Eric; Pottebaum, Jens; Fockel, Markus; Gräßler, Iris (IEEE Security & Privacy)
Keywords: Law; Electrical and Electronic Engineering; Computer Networks and Communications

Detecting Security-Relevant Methods using Multi-label Machine Learning - Johnson, Oshando; Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (Proceedings of the 46th International Conference on Software Engineering, IDE Workshop)
To detect security vulnerabilities, static analysis tools need to be configured with security-relevant methods. Current approaches can automatically identify such methods using binary relevance machine learning approaches. However, they ignore dependencies among security-relevant methods, over-generalize and perform poorly in practice. Additionally, users have to nevertheless manually configure static analysis tools using the detected methods. Based on feedback from users and our observations, the excessive manual steps can often be tedious, error-prone and counter-intuitive. In this paper, we present Dev-Assist, an IntelliJ IDEA plugin that detects security-relevant methods using a multi-label machine learning approach that considers dependencies among labels. The plugin can automatically generate configurations for static analysis tools, run the static analysis, and show the results in IntelliJ IDEA. Our experiments reveal that Dev-Assist's machine learning approach has a higher F1-Measure than related approaches. Moreover, the plugin reduces and simplifies the manual effort required when configuring and using static analysis tools.

Model Generation For Java Frameworks - Luo, Linghui; Piskachev, Goran; Krishnamurthy, Ranjith; Dolby, Julian; Schäf, Martin; Bodden, Eric (IEEE International Conference on Software Testing, Verification and Validation (ICST))

Eliciting Security Requirements – An Experience Report - Trentinaglia, Roman; Merschjohann, Sven; Fockel, Markus; Eikerling, Hendrik (REFSQ 2023: Requirements Engineering: Foundation for Software Quality)

Data-Driven Product Management: A Practitioner-Driven Research Agenda - Grigoryan, Khoren; Fichtler, Timm; Schreiner, Nick; Rabe, Martin; Panzner, Melina; Kühn, Arno; Dumitrescu, Roman; Koldewey, Christian (Procedia CIRP 33)
The global megatrends of digitization and sustainability lead to new challenges for the design and management of technical products in industrial companies. Product management - as the bridge between market and company - has the task to absorb and combine the manifold requirements and make the right product-related decisions. In the process, product management is confronted with heterogeneous information, rapidly changing portfolio components, as well as increasing product, and organizational complexity. Combining and utilizing data from different sources, e.g., product usage data and social media data leads to promising potentials to improve the quality of product-related decisions. In this paper, we reinforce the need for data-driven product management as an interdisciplinary field of action. The state of data-driven product management in practice was analyzed by conducting workshops with six manufacturing companies and hosting a focus group meeting with experts from different industries. We investigate the expectations and derive requirements leading us to open research questions, a vision for data-driven product management, and a research agenda to shape future research efforts.
Keywords: Product Management; Data Analytics; Data-Driven Design; Product-related data; Lifecycle Data; Tool-support

Echtzeitfähige Modellierung eines innovativen Drückwalzprozesses für die eigenschaftsgeregelte Bauteilfertigung - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (at - Automatisierungstechnik)
Zusammenfassung Aufgrund aktueller Transformationsprozesse kommt der automatisierten und ressourceneffizienten Fertigung hochfester Leichtbauteile eine steigende Bedeutung zu, beispielsweise im Flugzeug- und Fahrzeugbau. Für kleine Losgrößen bietet sich hier insbesondere das Fertigungsverfahren des Drückwalzens an. Der konventionelle, industriell genutzte Drückwalzprozess stößt allerdings aufgrund der Prozesskomplexität hinsichtlich der Reproduzierbarkeit an seine Grenzen. Dies wird in der Praxis teilweise durch personengebundenes Erfahrungswissen kompensiert. Auch ist es nicht möglich, Bauteileigenschaften definiert einzustellen. Aus diesem Grund bietet der Einsatz einer neuartigen Eigenschaftsregelung Chancen zur Weiterentwicklung des Fertigungsprozesses und die Möglichkeit zur Prozessautomatisierung. Hier werden die Werkzeugbahnen abhängig einer Online-Eigenschaftsmessung über eine zusätzliche Reglerkaskade manipuliert. Die Entwicklung einer solchen Eigenschaftsregelung erfordert den Einsatz geeigneter, modellbasierter Entwurfsmethoden. In diesem Beitrag wird daher ein regelungstechnisches Systemmodell für das Drückwalzen metastabiler austenitischer Edelstähle vorgestellt. Das Simulationsmodell weist aufgrund seiner Echtzeitfähigkeit neben dem Einsatz als reines Entwurfsmodell weitere Nutzungsmöglichkeiten z.B. in Beobachtern auf und grenzt sich somit von domänenspezifischen Simulationstools wie der FEM ab.
Keywords: Electrical and Electronic Engineering; Computer Science Applications; Control and Systems Engineering

Control strategy for angular gradations by means of the flow forming process - Kersting, Lukas; Arian, Bahman; Rozo Vasquez, Julian; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Materials Research Proceedings)
Abstract. Climate change, rare resources and industrial transformation processes lead to a rising demand of multi-complex lightweight forming parts, especially in aerospace and automotive sectors. In these industries, flow forming is often used to produce cylindrical forming parts by reducing the wall thickness of tubular semifinished parts, e.g. for the production of hydraulic cylinders or gear shafts. The complexity and functionality of flow forming workpieces could be significantly increased by locally graded microstructure and geometry structures. This enables customized complex hardness distributions at wear surfaces or magnetic QR codes for a unique, tamper-proof product identification. The production of those complex, 2D (axial and angular) graded forming parts currently depicts a great challenge for the process and requires new solutions and strategies. Hence, this paper proposes a novel control strategy that includes online measurements from an absolute encoder to determine the angular workpiece position. Workpieces of AISI 304L stainless steel with 2D-graded structures are successfully manufactured using this new strategy and analyzed regarding the possible accuracy and resolution of the gradation. At this point, a dependency of the gradations on the sensor and actuator dynamics, accuracy and geometry could be noted. It is further evaluated how the control strategy could be extended by an observer-based closed-loop property control approach to enhance the accuracy of the suggested strategy.

Detection of phase transformation during plastic deformation of metastable austenitic steel AISI 304L by means of X-ray diffraction pattern analysis - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar (Metals)

Novel Cascaded Incremental Nonlinear Dynamic Inversion Controller Approach for a Tiltrotor VTOL - Henkenjohann, Mark; Nolte, Udo; Henke, Christian; Trächtler, Ansgar (2023 International Conference on Unmanned Aircraft Systems (ICUAS))

Softsensor model of phase transformation during flow forming of metastable austenitic steel AISI 304L - Rozo Vasquez, Julian; Arian, Bahman; Kersting, Lukas; Walther, Frank; Homberg, Werner; Trächtler, Ansgar

Novel Straightening-Machine Design with Integrated Force Measurement for Straightening of High-Strength Flat Wire - Bathelt, Lukas; Scurk, Maximilian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Sensors)
In a punch-bending machine, wire products are manufactured for a wide range of industrial sectors, such as the electronics industry. The raw material for this process is flat wire made of high-strength steel. During the manufacturing process of the flat wire, residual stresses and plastic deformations are induced into the wire. These residual stresses and deformations fluctuate over the length of the semi-finished product and have a negative effect on the final product quality. Straightening machines are used to reduce this influence to a minimum. So far, the adjustment of a straightening machine has been performed manually, which is a lengthy and complex task even for an experienced worker. This inevitably leads to the use of inefficient straightening strategies and causes high rejection rates in the entire production process. Due to a lack of sensor information from the straightening operation, application of modern feedback control methods has not been practicable. This paper presents a novel design for a straightening machine with an integrated, precise straightening force measurement. By simultaneously monitoring the position of the straightening rollers, state variables of the straightening operation can be derived. Additionally, a tension control for feeding the flat wire is introduced. This is implemented to mitigate the disturbing effects caused by irregularities in the wire-feeding process. In the results of this article, the high precision of the developed force measurement design and its possible applications are shown.

A Methodical Approach to Hybrid Modelling for Contextual Anomaly Detection on Time-Series Data - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Innovative self-learning disturbance compensation for straightening processes - Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar (Materials Research Proceedings)
Abstract. To increase the sustainability of forming processes such as punch bending, homogenization of the processed semi-finished product is an essential step in the manufacturing process. High-strength wire materials are usually available as strip material before being further processed in a forming process. For storage and transport, the material is coiled onto coils and transported to the customer. During the coiling process, residual stresses and plastic deformation are introduced into the wire. Thus, the final product quality is also influenced by the geometry of the coil. Straightening machines are used in production lines to compensate for these. Once a straightening machine has been set up, the settings for the roll positions are usually not changed. As a result, there is no reaction to material fluctuations, which means that the components to be produced do not meet the dimensional accuracy requirements. This leads to an increase in the rejection rate in manufacturing processes. To reduce the rejection rate, it is necessary to enable dynamic and flexible infeed of the straightening rollers. In this context, an innovative control concept with disturbance compensation was developed for the straightening process. The disturbance compensation uses a disturbance model that predicts the change in bending curvature over the coil radius. With this prediction, the straightening machine can be adjusted specifically. The roller positions are adjusted by a subordinate position control. The additional feedback from measured geometric product properties from the following punching-bending process enables the straightening machine to be adjusted even in the case of unforeseen fluctuations in the material properties. In this way, it is possible to react to any material fluctuations as required. This novel, demand-oriented adjustment of the straightening machine is expected to result in a high increase in the efficiency of the production process and a reduction of the rejection rate.

Neuartiger Ansatz zum Richten von zwei- und dreidimensionalen Fehlern an einem Federdraht - Bathelt, Lukas; Djakow, Eugen; Dahms, Frederik; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Ilmenauer Federntag 2023: Neueste Erkenntnisse zu Funktion, Berechnung, Prüfung und Gestaltung von Federn und Werkstoffen)

Learning the Automated Setup of Profile Wrapping Lines for New Products from Few Past Setups - Koppert, Steven; Bause, Maximilian; Henke, Christian; Trächtler, Ansgar (2023 IEEE 21st International Conference on Industrial Informatics (INDIN))

Can the configuration of static analyses make resolving security vulnerabilities more effective? - A user study - Piskachev, Goran; Becker, Matthias; Bodden, Eric (Empirical Software Engineering)
Abstract The use of static analysis security testing (SAST) tools has been increasing in recent years. However, previous studies have shown that, when shipped to end users such as development or security teams, the findings of these tools are often unsatisfying. Users report high numbers of false positives or long analysis times, making the tools unusable in the daily workflow. To address this, SAST tool creators provide a wide range of configuration options, such as customization of rules through domain-specific languages or specification of the application-specific analysis scope. In this paper, we study the configuration space of selected existing SAST tools when used within the integrated development environment (IDE). We focus on the configuration options that impact three dimensions, for which a trade-off is unavoidable, i.e., precision, recall, and analysis runtime. We perform a between-subjects user study with 40 users from multiple development and security teams - to our knowledge, the largest population for this kind of user study in the software engineering community. The results show that users who configure SAST tools are more effective in resolving security vulnerabilities detected by the tools than those using the default configuration. Based on post-study interviews, we identify common strategies that users have while configuring the SAST tools to provide further insights for tool creators. Finally, an evaluation of the configuration options of two commercial SAST tools, Fortify and CheckMarx , reveals that a quarter of the users do not understand the configuration options provided. The configuration options that are found most useful relate to the analysis scope.
Keywords: Software

Concept for a cloud-based holistic energy management of domestic appliances to stabilize the energy supply and the power grid - Stieren, Stephan; Wichtrup, Moritz; Henke, Christian; Trächtler, Ansgar (NEIS - Conference on Sustainable Energy Supply and Energy Storage Systems)

Cryogenic reverse flow forming of AISI 304L - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank (Materials Research Proceedings)
Abstract. Workpiece property-control permits the application-oriented and time-efficient production of components. In reverse flow forming, for example, a control of the microstructure profile is not yet part of the state of the art, in contrast to the geometry control. This is, due to several reasons, particularly challenging when forming seamless tubes made of metastable austenitic stainless AISI 304L steel. Inducing mechanical and/or thermal energy can cause a phase transformation from austenite to martensite within this steel. The resulting α’-martensite has different mechanical and micromagnetic properties, which can be advantageous depending on the application. For purposes of local property control, the resulting α’-martensite content should be measured and controlled online during the forming process. This paper presents results from the usage of a custom developed cryo-system and different application strategies to use liquid nitrogen as a coolant for local enhancement of the forming-temperature depending α’-martensite content.

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Semi-automatic Integrated Safety and Security Analysis for Automotive Systems - Fockel, Markus; Schubert, David; Trentinaglia, Roman; Schulz, Hannes; Kirmair, Wolfgang (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Integrating Security Protocols in Scenario-based Requirements Specifications - Koch, Thorsten; Trippel, Sascha; Dziwok, Stefan; Bodden, Eric (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Domain-specific Language for Condition Monitoring Software Development - Pasic, Faruk; Becker, Matthias (2022 IEEE 27th International Conference on Emerging Technologies and Factory Automation (ETFA))

Deriving model-based safety and security assurance cases from design rationale of countermeasure patterns - Trentinaglia, Roman (Proceedings of the 25th International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

Early timing analysis based on scenario requirements and platform models - Holtmann, Jörg; Deantoni, Julien; Fockel, Markus (Software and Systems Modeling)
Distributed, software-intensive systems (e.g., in the automotive sector) must fulfill communication requirements under hard real-time constraints. The requirements have to be documented and validated carefully using a systematic requirements engineering (RE) approach, for example, by applying scenario-based requirements notations. The resources of the execution platforms and their properties (e.g., CPU frequency or bus throughput) induce effects on the timing behavior, which may lead to violations of the real-time requirements. Nowadays, the platform properties and their induced timing effects are verified against the real-time requirements by means of timing analysis techniques mostly implemented in commercial-off-the-shelf tools. However, such timing analyses are conducted in late development phases since they rely on artifacts produced during these phases (e.g., the platform-specific code). In order to enable early timing analyses already during RE, we extend a scenario-based requirements notation with allocation means to platform models and define operational semantics for the purpose of simulation-based, platform-aware timing analyses. We illustrate and evaluate the approach with an automotive software-intensive system.
Keywords: Modeling and Simulation; Software

Fluently specifying taint-flow queries with fluentTQL - Piskachev, Goran; Späth, Johannes; Budde, Ingo; Bodden, Eric (Empirical Software Engineering)

To what extent can we analyze Kotlin programs using existing Java taint analysis tools? - Krishnamurthy, Ranjith; Piskachev, Goran; Bodden, Eric

How far are German companies in improving security through static program analysis tools? - Piskachev, Goran; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven; Bodden, Eric

Analysis of Differential Algebraic Equation Systems for Connecting Energy Storages of Generally Valid Functional Mock-up Units - Ehlert, Meik; Henke, Christian; Trächtler, Ansgar (Proceedings of the 12th International Conference on Simulation and Modeling Methodologies, Technologies and Applications)

Innovative assistance system for setting up a mechatronic straightening machine - Bathelt, Lukas; Bader, Fabian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar; Homberg, Werner
High-strength wire materials are usually available as strip material which is further processed in a forming process (e.g. punch-bending). For storage and transport of the semi-finished wire to the customer, the material is wound onto coils. The manufacturing and coiling process introduces plastic deformations into the wire, which lead to undesirable residual stresses and wire curvature of the semi-finished product. These residual stresses and curvatures cause variations in the material properties of the semi-finished product, which have a negative impact on the subsequent product quality. Straightening machines are used to compensate the residual stresses and the curvature in the wire. At the beginning of the straightening process, the straightening machines must be set up in such a way that residual stresses and curvatures are optimally compensated. This setup process is usually a manual and iterative process, where a lot of material is wasted until the optimal settings for the straightening machine are found.In order to reduce the amount of material waste, the operator must be supported in the setup process. In this context, a new and innovative setup assistance system was developed to support the operator during the setup process. The setup assistant system automatically detects the wire curvature by means of an optical measuring system. Based on the optically detected measuring points, the wire curvature is determined by a robust calculation algorithm. Based on a database built up through the carried out experimental and numerical research work, the optimum setting parameters for the straightening machine are suggested to the operator without lengthy trial and error. After confirmation by the operator, the roller settings are automatically adjusted by the mechatronic straightening machine. With the presented method, the conventional iterative setup procedure can be made more resource-efficient and a high straightening quality can be reproducibly achieved.

An approach for an innovative 3d steel strip straightening machine for curvature and saber compensation - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Homberg, Werner; Trächtler, Ansgar
Due to increasing globalization and rising quality requirements, the steel and metal processing industry is facing growing cost and innovation pressure. Not least because of their high lightweight potential, high-strength steel materials are meeting the growing material requirements of steel and metal processing in areas such as aerospace and medical technology. In particular, the tight tolerance limits of applicable shape and dimensional accuracies pose a challenge in the processing of high-strength steel strip materials. Improving the processability of high-strength steel materials through the use of straighteners with set-up assistance systems significantly increases the potential for competing with other materials such as aluminum or magnesium alloys.

Tool Wear Monitoring of a Tree Log Bandsaw using a Deep Convolutional Neural Network on challenging data - Koppert, Steven; Henke, Christian; Trächtler, Ansgar; Möhringer, Stefan (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Mechatronische Richtapparate: Intelligente Richttechnik von hochfesten Flachdrähten - Bathelt, Lukas; Bader, Fabian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Fachtagung VDI MECHATRONIK 2022)

Virtual Commissioning of the Trajectory Tracking Control of a Sensor-Guided, Kinematically Redundant Robotic Welding System on a PLC - Schütz, Stefan; Schmidt, Robin; Henke, Christian; Trächtler, Ansgar (2022 IEEE International Systems Conference (SysCon))

Anomaly Detection in Hot Forming Processes using Hybrid Modeling - Part II - Lenz, Cederic; Hanke, Fabian; Henke, Christian; Trächtler, Ansgar (2022 27th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA ))

Coupled microscopic and micromagnetic depth-specific analysis of plastic deformation and phase transformation of metastable austenitic steel AISI 304L by flow forming - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents the characterization of the microstructure evolution during flow forming of austenitic stainless steel AISI 304L. Due to plastic deformation of metastable austenitic steel, phase transformation from γ-austenite into α’-martensite occurs. This is initiated by the formation of shear bands as product of the external stresses. By means of coupled microscopic and micromagnetic investigations, a characterization of the microstructure was carried out. In particular, this study shows the distribution of the strain-induced α’-martensite and its influence on material properties like hardness at different depths. The microstructural analyses by means of electron backscattered diffraction (EBSD) technique, evidence a higher amount of α’-martensite (ca. 23 %) close to the outer specimen surface, where the plastic deformation and the direct contact with the forming tool take place. In the middle area (ca. 1.5 mm depth from the outer surface), the portion of transformed α’-martensite drops to 7 % and in the inner surface to 2 %. These results are well correlated with microhardness and micromagnetic measurements at different depths. EBSD and atomic force microscopy (AFM) were used to make a detailed characterization of the topography and degree of deformation of the shear bands. Likewise, the mechanisms of nucleation of α’-martensite were discussed. This research contributes to the development of micromagnetic sensors to monitor the evolution of properties during flow forming. This makes them more suitable for closed-loop property control, which offers possibilities for an application-oriented and more efficient production.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Innovative Online Measurement and Modelling Approach for Property-Controlled Flow Forming Processes - Kersting, Lukas; Arian, Bahman; Vasquez, Julian Rozo; Trächtler, Ansgar; Homberg, Werner; Walther, Frank (Key Engineering Materials)
The production of complex multi-functional, high-strength parts is becoming increasingly important in the industry. Especially with small batch size, the incremental flow forming processes can be advantageous. The production of parts with complex geometry and locally graded material properties currently depicts a great challenge in the flow forming process. At this point, the usage of closed-loop control for the shape and properties could be a feasible new solution. The overall aim in this project is to establish an intelligent closed-loop control system for the wall thickness as well as the α’-martensite content of AISI 304L-workpieces in a flow forming process. To reach this goal, a novel sensor concept for online measurements of the wall thickness reduction and the martensite content during forming process is proposed. It includes the setup of a modified flow forming machine and the integration of the sensor system in the machine control. Additionally, a simulation model for the flow forming process is presented which describes the forming process with regard to the plastic workpiece deformation, the induced α’-martensite fraction, and the sensor behavior. This model was used for designing a closed-loop process control of the wall thickness reduction that was subsequently realized at the real plant including online measured feedback from the sensor system.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Soft sensor concept for micromagnetic depth-specific analysis of phase transformation during flow forming of AISI 304L steel. - Rozo Vasquez, Julian; Walther, Frank; Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar (Proceedings of the 14th International Conference on Barkhausen Noise and Micromagnetic Testing)

Echtzeitfähige Modellierung eines innovativen Drückwalzprozesses für die eigenschaftsgeregelte Herstellung gradierter Bauteile. - Kersting, Lukas; Trächtler, Ansgar; Arian, Bahman; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank

Regelungstechnik. Einführung in die Methoden und ihre Anwendung - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

Towards the Concept of a Digital Green Twin for a Sustainable Product Lifecycle - Michael, Jan; Grote, Eva-Maria; Pfeifer, Stefan; Rasor, Rik; Henke, Christian; Trächtler, Ansgar; Kaiser, Lydia

Connecting Energy Storages from Tool Independent, Signal-flow Oriented FMUs - Ehlert, Meik; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Kalla, Matthias; Bagaber, Bakr; Ponick, Bernd; Mertens, Axel (Proceedings of the International Conference on SMACD and 16th Conference on PRIME)

Model of a Triangular Caterpillar Drive and Analysis of Vertical Vehicle Dynamics - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Russian Engineering Research)

Cutting through the Jungle: Disambiguating Model-based Traceability Terminology (Extended Abstract) - Holtmann, Jörg; Steghöfer, Jan-Phillipp; Rath, Michael; Schmelter, David (Software Engineering 2021)

Application-Aware Intrusion Detection: A Systematic Literature Review, Implications for Automotive Systems, and Applicability of AutoML - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (Frontiers in Computer Science)
Modern and flexible application-level software platforms increase the attack surface of connected vehicles and thereby require automotive engineers to adopt additional security control techniques. These techniques encompass host-based intrusion detection systems (HIDSs) that detect suspicious activities in application contexts. Such application-aware HIDSs originate in information and communications technology systems and have a great potential to deal with the flexible nature of application-level software platforms. However, the elementary characteristics of known application-aware HIDS approaches and thereby the implications for their transfer to the automotive sector are unclear. In previous work, we presented a systematic literature review (SLR) covering the state of the art of application-aware HIDS approaches. We synthesized our findings by means of a fine-grained classification for each approach specified through a feature model and corresponding variant models. These models represent the approaches’ elementary characteristics. Furthermore, we summarized key findings and inferred implications for the transfer of application-aware HIDSs to the automotive sector. In this article, we extend the previous work by several aspects. We adjust the quality evaluation process within the SLR to be able to consider high quality conference publications, which results in an extended final pool of publications. For supporting HIDS developers on the task of configuring HIDS analysis techniques based on machine learning, we report on initial results on the applicability of AutoML. Furthermore, we present lessons learned regarding the application of the feature and variant model approach for SLRs. Finally, we more thoroughly describe the SLR study design.

AppSecure.nrw Software Security Study - Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven; Budweg, Boris; Leuer, Sebastian (arXiv:2108.11752)
In recent years, the World Economic Forum has identified software security as the most significant technological risk to the world's population, as software-intensive systems process critical data and provide critical services. This raises the question of the extent to which German companies are addressing software security in developing and operating their software products. This paper reports on the results of an extensive study among developers, product owners, and managers to answer this question. Our results show that ensuring security is a multi-faceted challenge for companies, involving low awareness, inaccurate self-assessment, and a lack of competence on the topic of secure software development among all stakeholders. The current situation in software development is therefore detrimental to the security of software products in the medium and long term.

A Meta-Review on Artiﬁcial Intelligence in Product Creation - Bernijazov, Ruslan; Dicks, Alexander; Dumitrescu, Roman; Foullois, Marc; Hanselle, Jonas Manuel; Hüllermeier, Eyke; Karakaya, Gökce; Ködding, Patrick; Lohweg, Volker; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Panzner, Melina; et al. (Proceedings of the 30th International Joint Conference on Artificial Intelligence (IJCAI-21))
Produktentstehung (PE) bezieht sich auf den Prozess der Planung und Entwicklung eines Produkts sowie der damit verbundenen Dienstleistungen von der ersten Idee bis zur Herstellung und zum Vertrieb. Während dieses Prozesses gibt es zahlreiche Aufgaben, die von menschlichem Fachwissen abhängen und typischerweise von erfahrenen Experten übernommen werden. Da sich das Feld der Künstlichen Intelligenz (KI) immer weiterentwickelt und seinen Weg in den Fertigungssektor findet, gibt es viele Möglichkeiten für eine Anwendung von KI, um bei der Lösung der oben genannten Aufgaben zu helfen. In diesem Paper geben wir einen umfassenden Überblick über den aktuellen Stand der Technik des Einsatzes von KI in der PE. Im Detail analysieren wir 40 bestehende Surveys zu KI in der PE und 94 Case Studies, um herauszufinden, welche Bereiche der PE von der aktuellen Forschung in diesem Bereich vorrangig adressiert werden, wie ausgereift die diskutierten KI-Methoden sind und inwieweit datenzentrierte Ansätze in der aktuellen Forschung genutzt werden.
Keywords: Artificial Intelligence Product Creation Literature Review

Kraftsensitive Kalibriermethode für Industrieroboter - Schütz, Stefan; Elsner, Nikolaus; Henke, Christian; Trächtler, Ansgar (Fachtagung VDI MECHATRONIK 2021)

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Robotersysteme auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (at-Automatisierungstechnik)

Qualitative and Quantitative Analysis of Callgraph Algorithms for Python - Kummita, Sriteja; Piskachev, Goran; Spath, Johannes; Bodden, Eric (2021 International Conference on Code Quality (ICCQ))

The MobSTr Dataset – An Exemplar for Traceability and Model-based Safety Assessment - Steghofer, Jan-Philipp; Koopmann, Bjorn; Steffen Becker, Jan; Stierand, Ingo; Zeller, Marc; Bonner, Maria; Schmelter, David; Maro, Salome (2021 IEEE 29th International Requirements Engineering Conference (RE))

SecuCheck: Engineering configurable taint analysis for software developers - Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Magnetic Barkhausen noise analysis for microstructural effects separation during flow forming of metastable austenite 304L. - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Walther, Frank; Homberg, Werner; Trächtler, Ansgar (Proceedings of the 11th International Workshop NDT in Progress)

Forming of metastable austenitic stainless steel tubes with axially graded martensite content by flow-forming - Arian, Bahman; Homberg, Werner; Riepold, Markus; Trächtler, Ansgar; Rozo Vasquez, Julian; Walther, Frank
One of the main objectives of production engineering is to reproducibly manufacture (complex) defect-free parts. To achieve this, it is necessary to employ an appropriate process or tool design. While this will generally prove successful, it cannot, however, offset stochastic defects with local variations in material properties. Closed-loop process control represents a promising approach for a solution in this context. The state of the art involves using this approach to control geometric parameters such as a length. So far, no research or applications have been conducted with closed-loop control for microstructure and product properties. In the project on which this paper is based, the local martensite content of parts is to be adjusted in a highly precise and reproducible manner. The forming process employed is a special, property-controlled flow-forming process. A model-based controller is thus to generate corresponding correction values for the tool-path geometry and tool-path velocity on the basis of online martensite content measurements. For the controller model, it is planned to use a special process or microstructure (correlation) model. The planned paper not only describes the experimental setup but also presents results of initial experimental investigations for subsequent use in the closed-loop control of α’-martensite content during flow-forming.
Keywords: Flow-forming; Spinning; Process Strategy; Martensite Content; Property Control; Micromagnetic Measurement; Metastable Austenitic Stainless Steel

Anomaly detection in hot forming processes using hybrid modeling - Lenz, Cederic; Henke, Christian; Trächtler, Ansgar (2021 26th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

Model approaches for closed-loop property control for flow forming - Riepold, Markus; Arian, Bahman; Vasquez, Julian Rozo; Homberg, Werner; Walther, Frank; Trächtler, Ansgar (Advances in Industrial and Manufacturing Engineering)
The implementation of control systems in metal forming processes improves product quality and productivity. By controlling workpiece properties during the process, beneficial effects caused by forming can be exploited and integrated in the product design. The overall goal of this investigation is to produce tailored tubular parts with a defined locally graded microstructure by means of reverse flow forming. For this purpose, the proposed system aims to control both the desired geometry of the workpiece and additionally the formation of strain-induced α′-martensite content in the metastable austenitic stainless steel AISI 304 L. The paper introduces an overall control scheme, a geometry model for describing the process and changes in the dimensions of the workpiece, as well as a material model for the process-induced formation of martensite, providing equations based on empirical data. Moreover, measurement systems providing a closed feedback loop are presented, including a novel softsensor for in-situ measurements of the martensite content.

Mechanical and mathematical model of a caterpillar drive with a triangular contour for solving problems of vertical dynamics of a tracked vehicle - Poddubnyi, Vladimir I.; Trächtler, Ansgar; Warkentin, Andreas; Henke, Christian (Vestnik Mashinostroeniya)

Cutting through the Jungle: Disambiguating Model-based Traceability Terminology - Holtmann, Jörg; Steghofer, Jan-Philipp; Rath, Michael; Schmelter, David (2020 IEEE 28th International Requirements Engineering Conference (RE))
Traceability, a classic requirements engineering topic, is increasingly used in the context of model-based engineering. However, researchers and practitioners lack a concise terminology to discuss aspects of requirements traceability in situations in which engineers heavily rely on models and model-based engineering. While others have previously surveyed the domain, no one has so far provided a clear, unambiguous set of terms that can be used to discuss traceability in such a context. We therefore set out to cut a path through the jungle of terminology for model-based traceability, ground it in established terminology from requirements engineering, and derive an unambiguous set of relevant terms. We also map the terminology used in existing primary and secondary studies to our taxonomy to show differences and commonalities. The contribution of this paper is thus a terminology for model-based traceability that allows requirements engineers and engineers working with models to unambiguously discuss their joint traceability efforts.

Scenario-based Specification of Security Protocols and Transformation to Security Model Checkers - Koch, Thorsten; Dziwok, Stefan; Holtmann, Jörg; Bodden, Eric (ACM/IEEE 23rd International Conference on Model Driven Engineering Languages and Systems (MODELS ’20))

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Mechanismen auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Entwurf komplexer Automatisierungssysteme (EKA))

Language-agnostic Injection Detection - Hermerschmidt, Lars; Straub, Andreas; Piskachev, Goran (2020 IEEE Security and Privacy Workshops (SPW))

SWAN_ASSIST: Semi-Automated Detection of Code-Specific, Security-Relevant Methods - Piskachev, Goran; Nguyen Quang Do, Lisa; Johnson, Oshando; Bodden, Eric (2019 34th IEEE/ACM International Conference on Automated Software Engineering (ASE))

AuthCheck: Program-State Analysis for Access-Control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (Lecture Notes in Computer Science)

Softwareentwicklung wie am Fliessband - Koch, Thorsten; Meyer, Matthias; Fazal-Baqaie, Masud; Runschke, Hubert (Software Engineering 2020 (SE 2020))

Mechatronischer Entwurf eines geregelten Federungssystems für mittelschwere gepanzerte Kettenfahrzeuge - Gense, Alexander

Produkttolerante Automation zellenbasierter Fertigungssysteme - Bertelsmeier, Fabian

Microstructural investigation on phase transformation during flow forming of the metastable austenite AISI 304 - Rozo Vasquez, Julian; Arian, Bahman; Riepold, Markus; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (54. Metallographie-Tagung)

A KPI-based Condition Monitoring System for the Beer Brewing Process - Pasic, Faruk; Wohlers, Benedict; Dziwok, Stefan; Becker, Matthias; Heinrich, Matthias (2019 24th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA))

AuthCheck: Program-state Analysis for Access-control Vulnerabilities - Piskachev, Goran; Petrasch, Tobias; Späth, Johannes; Bodden, Eric (10th Workshop on Tools for Automatic Program Analysis (TAPAS))

Coaching on the Job bei Unternehmen des Maschinen- und Anlagenbaus - Wissenslücken schließen zur Weiterpflege modernisierter IT-Anwendungen - Fazal-Baqaie, Masud; Strüwer, Jan-Niclas; Schmelter, David; Dziwok, Stefan (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Improvement of Software Requirements Quality based on Systems Engineering - Holtmann, Jörg

Component-Based Refinement and Verification of Information-Flow Security Policies for Cyber-Physical Microservice Architectures - Gerking, Christopher; Schubert, David (International Conference on Software Architecture (ICSA 2019))

Application-aware Intrusion Detection: A Systematic Literature Review and Implications for Automotive Systems - Schubert, David; Eikerling, Hendrik; Holtmann, Jörg (17th escar Europe : embedded security in cars)

Monitoring and Control of Production Processes based on Key Performance Indicators for Mechatronic Systems - Wohlers, Benedict; Dziwok, Stefan; Pasic, Faruk; Lipsmeier, Andre; Becker, Matthias (International Journal of Production Economics)
The processes for manufacturing and operating modern technical products require expertise in multiple disciplines like mechanical engineer-ing, electrical engineering, and software engineering. Assessing the current condition and quality of these processes and the machines in-volved is challenging due to the inherent complexity of the products and the required expertise in multiple engineering domains. Globaliza-tion and increasing competition make it necessary to reduce production costs while at the same time ensuring high throughput and product quality. Without the ability to precisely assess the condition and quality of production processes and involved machines, taking action to steer these metrics is nearly impossible and results in unnecessary high production costs. In our previous publications, we introduced the concept of Key Performance Indicators (KPIs) for mechatronic systems as a concept to assess the condition and quality of products and production processes in a graspable yet substantial and efficient way. In this paper, we further refine our KPI concepts und evaluate them for two different use cases: we apply our KPI concept to a manufacturing process in the mechatronic system domain and an operation process in the food production domain. We provide detailed insights in how we applied our concepts within these domains and report about lessons learned. In addition, we provide a business case estimation for our soft-ware solution that assesses the KPIs of our food production domain example.

Designing and Integrating IEC 62443 Compliant Threat Analysis - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud; Förder, Torsten; Hausmann, Stefan; Waldeck, Boris (European System, Software & Service Process Improvement & Innovation Conference (EuroSPI 2019))

Assisted setup of forming processes: architecture for the integration of non-adjustable disturbances - Gräler, Manuel; Wallow, Astrid; Henke, Christian; Trächtler, Ansgar (Procedia CIRP)

Decentralized Energy Management for Smart Home System of Systems - Michael, Jan; Henke, Christian; Trächtler, Ansgar (Syscon 2019 - The 13th Annual IEEE International Systems Conference)

Regelung kollaborativer Robotersysteme zur benutzerfreundlichen, flexiblen Fertigung kleiner Losgrößen am Beispiel eines halbautomatischen Schweißvorgangs - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (Fachtagung Mechatronik 2019)

Open-loop linearization for piezoelectric actuator with inverse hysteresis model - Riepold, Markus; Maslo, Semir; Han, Ge; Henke, Christian; Trächtler, Ansgar (Vibroengineering PROCEDIA)

Umsetzung einer echtzeitfähigen modellprädiktiven Trajektorienplanung für eine mehrachsige Hybridkinematik auf einer Industriesteuerung - Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (at-Automatisierungstechnik)

Codebase-adaptive detection of security-relevant methods - Piskachev, Goran; Do, Lisa Nguyen Quang; Bodden, Eric (Proceedings of the 28th ACM SIGSOFT International Symposium on Software Testing and Analysis)

Was fehlt (bisher) um Apps sicher zu entwickeln? - Prozesse, Werkzeuge und Schulungen für sichere Apps by Design - Altemeier, Katharina; Becker, Matthias; Dziwok, Stefan; Koch, Thorsten; Merschjohann, Sven (Projektmanagement und Vorgehensmodelle 2019 (PVM 2019))

Model-driven development of condition monitoring software - Pasic, Faruk (Proceedings of the 21st ACM/IEEE International Conference on Model Driven Engineering Languages and Systems: Companion Proceedings)

Safety Requirements Engineering for Early SIL Tailoring - Fockel, Markus
Der hohe Grad an Innovation in mechatronischen Systemen führt zu sogenannten Cyber-Physical Systems (CPS). Diese haben eine komplexe Funktionalität und Kommunikation. Wie sicherheitskritisch solche Systeme sind, wird durch sogenannte Sicherheits-Integritätslevel (SIL) kategorisiert, die durch Normen wie der ISO 26262 definiert werden. Ein bestimmter SIL beschreibt nicht nur die Höhe des Gefährdungsrisikos, sondern diktiert auch den erforderlichen Grad an Sorgfalt bei der Entwicklung des Systems. Ein hoher SIL erfordert die Anwendung von Safety-Maßnahmen mit einem hohen Sorgfaltsgrad in allen Phasen der Entwicklung und impliziert daher einen hohen Safety-Aufwand. SIL-Tailoring ist ein Mittel um den Safety-Aufwand zu reduzieren, indem man Subsystemen geringere SILs zuordnet, falls sie von kritischeren Subsystemen getrennt sind oder redundante Safety-Anforderungen erfüllen. Um den nötigen Safety-Aufwand zu planen, sollten Möglichkeiten für SIL-Tailoring so früh wie möglich identifiziert werden - d.h. bereits in der Anforderungsanalyse. Durch die Komplexität von CPS, ist es schwierig valide SIL-Tailorings zu finden. Die Validität von SIL-Tailorings muss durch Analyse von Fehlerpropagierungspfaden geprüft und durch Argumente im Safety Case begründet werden. Der Beitrag dieser Dissertation ist ein systematischer, tool-unterstützter SIL-Tailoring-Prozess, der im Safety Requirements Engineering angewendet wird. Der Prozess nutzt eine modell-basierte, formale Anforderungsspezifikation und stellt einen Katalog von Anforderungsmustern bereit. Basierend auf diesen Anforderungen werden Fehlerpropagierungsmodelle generiert und Subsystemen automatisch SILs zugeordnet. Das minimiert den Sicherheitsanalyseaufwand. Aus den generierten Ergebnissen wird automatisch ein Safety Case mit Argumenten für die SIL-Tailoring-Validität abgeleitet.

Threat Analysis in Practice - Systematically Deriving Security Requirements - Fockel, Markus; Merschjohann, Sven; Fazal-Baqaie, Masud (19th International Conference on Product-Focused Software Process Improvement (PROFES 2018))
With the growing number of incidents, the topic security gains more and more attention across all domains. Organizations realize their lack of state-of-the-art security practices, however, they struggle to improve their software lifecycle in terms of security. In this talk, we introduce the concept of security by design that implements security practices within the whole software lifecycle. Based on our practical experience from industry projects in the regulated industrial automation and unregulated classical IT domain, we explain how to perform a threat analysis and how to integrate it into the software lifecycle.

Towards Preserving Information Flow Security on Architectural Composition of Cyber-Physical Systems - Gerking, Christopher; Schubert, David (European Conference on Software Architecture (ECSA 2018))

Model-Driven STEP Application Protocol Extensions Combined with Feature Modeling Considering Geometrical Information - Koch, Thorsten; Holtmann, Jörg; Lindemann, Timo (Revised Selected Papers of the 5th International Conference on Model-Driven Engineering and Software Development)
Original equipment manufacturers (OEMs) build mechatronic, variant-rich systems using components from several suppliers in industry sectors like automation. The OEMs have to integrate the different components to the overall system based on a virtual layout. For this purpose, the suppliers provide geometrical information via the standardized exchange format STEP. Beyond the geometrical information, the OEMs need additional logical and technical information for the integration task as well as the variant handling. For that reason, STEP provides an extension mechanism for extending and tailoring STEP to project-specific needs. However, extending STEP requires extending several capabilities of all involved tools, which prevents the project-specific utilization of the STEP extensions mechanism. In order to cope with this problem, we presented in previous work a model-driven approach enabling the flexible specification of STEP extensions and particularly the automatic derivation of the required capability extensions for two involved tools. Nevertheless, the OEMs still need to apply several engineering tools from different domains to consider logical as well as geometrical constraints between product variants. In this paper, we hence combine our previous approach with extended feature models that consider conventional logical and particularly geometrical information, thereby enabling a holistic product line engineering for mechatronic systems. By means of an automation production system example, we illustrate how OEMs can orchestrate their overall supply and development processes through the combination of both approaches.

Towards Scenario-based Security Requirements Engineering for Cyber-Physical Systems - Koch, Thorsten (International Workshop on Security for and by Model-Driven Engineering (SecureMDE 2018))

Automated Synthesis of a Real-Time Scheduling for Cyber-Physical Multi-core Systems - Geismann, Johannes; Höttger, Robert; Krawczyk, Lukas; Pohlmann, Uwe; Schmelter, David (Model-Driven Engineering and Software Development)
Cyber-physical Systems are distributed, embedded systems that interact with their physical environment. Typically, these systems consist of several Electronic Control Units using multiple processing cores for the execution. Many systems are applied in safety-critical contexts and have to fulfill hard real-time requirements. The model-driven engineering paradigm enables system developers to consider all requirements in a systematical manner. In the software design phase, they prove the fulfillment of the requirements using model checking. When deploying the software to the executing platform, one important task is to ensure that the runtime scheduling does not violate the verified requirements by neglecting the model checking assumptions. Current model-driven approaches do not consider the problem of deriving feasible execution schedules for embedded multi-core platforms respecting hard real-time requirements. This paper extends the previous work on providing an approach for a semi-automatic synthesis of behavioral models into a deterministic real-time scheduling. We add an approach for the partitioning and mapping development tasks. This extended approach enables the utilization of parallel resources within a single ECU considering the verification assumptions by extending the open tool platform App4mc. We evaluate our approach using an example of a distributed automotive system with hard real-time requirements specified with the MechatronicUML method.

Formal, Model- and Scenario-based Requirement Patterns - Fockel, Markus; Holtmann, Jörg; Koch, Thorsten; Schmelter, David (6th International Conference on Model-Driven Engineering and Software Development (MODELSWARD 2018))
Distributed, software-intensive systems such as automotive electronic control units have to handle various situations employing message-based coordination. The growing complexity of such systems results in an increasing difficulty to achieve a high quality of the systems' requirements specifications. Scenario-based requirements engineering addresses the message-based coordination of such systems and enables, if underpinned with formal modeling languages, automatic analyses for ensuring the quality of requirements specifications. However, formal requirements modeling languages require high expertise of the requirements engineers and many manual iterations until specifications reach high quality. Patterns provide a constructive means for assembling high-quality solutions by applying reusable and established building blocks. Thus, they also gained momentum in requirements documentation. In order to support the requirements engineers in the systematic conception of formal, scenario-based requirements specification models, we hence introduce in this paper a requirement pattern catalog for a requirements modeling language. We illustrate and discuss the application of the requirement patterns with an example of requirements for an automotive electronic control unit.

Improving Quality Control of Mechatronic Systems Using KPI-Based Statistical Process Control - Wohlers, Benedict; Dziwok, Stefan; Schmelter, David; Lorenz, Wadim (Advances in Manufacturing, Production Management and Process Control - AHFE 2018)

Model-driven allocation engineering: specifying and solving constraints based on the example of automotive systems - Pohlmann, Uwe; Hüwe, Marcus (Automated Software Engineering)
Automotive systems provide sophisticated functionality and are controlled by networked electronic control units (ECUs). Nowadays, software engineers use component-based development approaches to develop their software. Moreover, software components have to be allocated to ECUs to be executed. Engineers have to cope with topology-, software-, and timing dependencies and memory-, scheduling-, and routing constraints. Currently, engineers use linear programming to specify allocation constraints manually and to compute a feasible allocation specification automatically. However, encoding the allocation problem as a linear program is a complex and error-prone task. This paper contributes a model-driven, object constraint language based, and graph pattern based allocation engineering approach for reducing the engineering effort and to avoid failures. We validate our approach with an automotive case study. We specify the software component model, the hardware platform model, and the allocation constraint specification with our engineering approach MechatronicUML. Our validation shows that we can specify allocation constraints with less engineering effort and are able to compute feasible allocation specifications automatically.

Rotordynamic instabilities in washing machines - Drüke, Simon; Bicker, Rainer; Schullter, Bernd; Henke, Christian; Trächtler, Ansgar (Proceedings of the 10th International Conference on Rotor Dynamics - IFToMM. Vol. 2. International Conference on Rotor Dynamics - IFToMM)

Assisted setup of forming processes: compensation of initial stochastic disturbances - Gräler, Manuel; Springer, Robert; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Swedish Production Symposium)

Umsetzung einer echtzeitfähigen Mehrgrößenoptimierung auf einer Industriesteuerung - Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (EKA 2018 Entwurf komplexer Automatisierungssysteme - Beschreibungsmittel, Methoden, Werkzeuge und Anwendungen)

Model based Setup Assistant for Progressive Tools - Springer, Robert; Graeler, Manuel; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (AIP Conference Proceedings)

Recent Developments in Hardware-in-the-Loop Testing - Millitzer, Jonathan; Mayer, Dirk; Jersch, Torben; Henke, Christian; Michael, Jan; Tamm, Christoph; Ranisch, Christopher (IMAC-XXXVI Conference and Exposition on Structural Dynamics)